AME de estratégia e liderança. Competências organizacionais e vantagem competitiva: o desafio da gerência intermediária - King, Adelaide Wilcox (2002)
Although most managers recognize that a firm’s competencies are an important source of competitive advantage, many firms encounter difficulties when they attempt to identify and assess those competencies. Specific competencies are often ambiguous to managers, and individual perceptions of a firm’s competencies may vary significantly. This lack of specificity may mask significant misunderstanding and confusion about competencies. When this misunderstanding or confusion occursamong middle managers who are responsible for the day-to-day management of these competencies, the implications for an organization can be serious. We identify and examine key characteristics of competencies and the relationship between middle managers’ perceptions of competencies and firm performance. We report a study of middle managers at 17 organizations in two industries: textile manufacturing and hospitals. Results demonstrate the linkages between competencycharacteristics and firm success. In addition, we describe a method that any firm can use to assess its competencies, and we show how management can use the assessment to enhance the firm’s competitive advantage.